Evaluation of Decalcification Techniques for Rat Femurs Using HE and Immunohistochemical Staining. (26th January 2017) - Liu, Haixia; Zhu, Ruyuan; Liu, Chenyue; Ma, Rufeng; Wang, Lili; Chen, Beibei; Li, Lin; Niu, Jianzhao; Zhao, Dandan; Mo, Fangfang; Fu, Min; Brömme, Dieter; et al.
Abstract : Aim . In routine histopathology, decalcification is an essential step for mineralized tissues. The purpose of this study is to evaluate the effects of different decalcification solutions on the morphological and antigenicity preservation in Sprague Dawley (SD) rat femurs. Materials and Methods . Four different decalcification solutions were employed to remove the mineral substances from rat femurs, including 10% neutral buffered EDTA, 3% nitric acid, 5% nitric acid, and 8% hydrochloric acid/formic acid. Shaking and low temperature were used to process the samples. The stainings of hematoxylin-eosin (HE) and immunohistochemical (IHC) were employed to evaluate the bone morphology and antigenicity. Key Findings . Different decalcification solutions may affect the quality of morphology and the staining of paraffin-embedded sections in pathological examinations. Among four decalcifying solutions, 3% nitric acid is the best decalcifying agent for HE staining. 10% neutral buffered EDTA and 5% nitric acid are the preferred decalcifying agents for IHC staining. Significance . The current study investigated the effects of different decalcifying agents on the preservation of the bone structure and antigenicity, which will help to develop suitable protocols for the analyses of the bony tissue.